My Abstract Word. - Dax, Max; Olbricht, Thomas; Rust, Julia; Sonderkamp, Sarah (Berlin : me Collectors Room, 2016)
Adnan, Etel ; Alsoudani, Ahmed ; Armleder, John M. ; Baer, Jo ; Banisadr, Ali ; Bill, Max ; Brierley, GL ; Butzer, André ; Chen, Shen ; Chun, Ouyang ; Demitz, Albrecht ; Fägerskiöld, Paul ; Flood, Mark ; Frize, Bernard ; Golder, Andreas et al.
How do I transform an exhibition building into a realm of artistic experience that appeals to all the senses? How do I create a space where people are able to concentrate, while simultaneously fostering a lively and relaxed atmosphere? The collector Thomas Olbricht has been looking for answers to these questions and developing new ideas ever since he first got involved in putting on exhibitions at me Collectors Room in Berlin. (Preface of the book)
My Abstract World, me Collectors Room Berlin, Berlin, 14.09.2016 - 02.04.2017
Music and art publicist Max Dax has made a music compilation in direct reponse to the selected artworks featured in the exhibition "My Abstract World" which visitors can hear via tghe app.
boek